2015
DOI: 10.1016/j.stemcr.2015.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Expansion, Enhanced Chondrogenic Potential, and Suppression of Endochondral Ossification of Adult Human MSCs via WNT Signaling Modulation

Abstract: SummaryMesenchymal stem cells (MSCs) are a potential source of chondrogenic cells for the treatment of cartilage disorders, but loss of chondrogenic potential during in vitro expansion and the propensity of cartilage to undergo hypertrophic maturation impede their therapeutic application. Here we report that the signaling protein WNT3A, in combination with FGF2, supports long-term expansion of human bone marrow-derived MSCs. The cells retained their chondrogenic potential and other phenotypic and functional pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
117
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(131 citation statements)
references
References 59 publications
14
117
0
Order By: Relevance
“…Overexpression of WNT/β-catenin signaling induces chondrocyte hypertrophy [42,46] while blocking WNT signaling using a WNT inhibitor during the last steps of chondrogenic differentiation prevents hypertrophic differentiation of the cells [23]. We proved our hypothesis that the endogenous WNT inhibitors DKK1 and FRZB play a determining role in preventing terminal chondrocyte differentiation by regulating WNT/β-catenin signaling.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Overexpression of WNT/β-catenin signaling induces chondrocyte hypertrophy [42,46] while blocking WNT signaling using a WNT inhibitor during the last steps of chondrogenic differentiation prevents hypertrophic differentiation of the cells [23]. We proved our hypothesis that the endogenous WNT inhibitors DKK1 and FRZB play a determining role in preventing terminal chondrocyte differentiation by regulating WNT/β-catenin signaling.…”
Section: Discussionmentioning
confidence: 54%
“…So the correct regulation of the WNT signaling plays an important role in the maintenance of the chondrogenic potential, as well as in suppression of endochondral ossification [23]. However, the mechanism by which WNT signaling is regulated in vivo is as yet unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by this report, Narcisi et al observed that combined pretreatment with Wnt3a greatly promoted the effect of FGF2 on human BMSC proliferation by increasing cell doublings from 20 to 30. They also found that co-preconditioned cells acquired enhanced chondrogenic potential; inhibition of Wnt3 signals during differentiation prevented calcification while preserving hyaline cartilage properties following transplantation in a mouse model [99]. In a three-dimensional (3D) pellet model, intriguingly, Centola et al found that, contrary to their initial hypothesis, Wnt3a treatment induced human BMSCs to a five-fold increase in cell number despite a continuing decrease of total DNA content in the 3D construct; preconditioning with Wnt3a improved cells’ chondrogenic potential, which was antagonized by treatment with FGF2 [100].…”
Section: Fgf Preconditioningmentioning
confidence: 99%
“…β-catenin forms a complex with DNA-binding T-cell factors (TCFs) to activate the transcription of target genes. The β-catenin signaling pathway often crosstalks with other signaling pathways to modulate chondrogenesis [1318]. However, the Wnt/β-catenin signaling pathway plays a crucial role in the hypertrophic maturation of chondrocytes during the endochondral ossification process [19].…”
Section: Introductionmentioning
confidence: 99%